A review of engine performance and emissions using single and dual biodiesel fuels: research paths, challenges, motivations and recommendations - Altarazi, Yazan S.M.; Abu Talib, Abd Rahim; Yusaf, Talal; Yu, Jianglong; Gires, Ezanee; Abdul Ghafir, Mohd Fahmi; Lucas, John (Elsevier, 2022)
Current research focuses on finding environmentally friendly energy sources as an alternative to fossil fuels due to declining resources with increasing population growth. This study identifies and summarises recent studies into the effect of biodiesel blends on engine performance and provides a classification of the literature. This study also aims to clarify the incentives for using biodiesel and the challenges still faced by researchers. Articles on biodiesel fuel and its blends in diesel and gas-turbine engines were collated and filtered based on the blending methods (complete substitution without diesel or partial substitution). Biodiesel utilization in gas turbines and its competitiveness with Jet fuel performance is one of the things that this study touched upon. Despite that, the gaps in using biodiesel instead of Jet-A still exist in turbine engines, so settling the challenges of using biodiesel in the aviation sector could be through using additives or substitutes. A total of 72 articles were selected and divided into two groups: single biodiesel blends and dual blend biodiesel. The fuel used and the engine types were identified for all articles, and the emission results and engine performance when biodiesel was used. This study contributes to the development and research into the primary system (such as compressor, combustion chamber, or turbine), challenges, and the limitations of the current studies.